2004
DOI: 10.1097/00006324-200402000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Astigmatism in Taiwan Schoolchildren

Abstract: Most schoolchildren had little or no astigmatism. In Taiwan, most astigmatism is <1 D and is myopic with-the-rule astigmatism. There was more myopic astigmatism and with-the-rule astigmatism in 2000 than in 1995.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
55
3
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 19 publications
8
55
3
1
Order By: Relevance
“…As previously reported in other studies, 1,2,21 with-the-rule astigmatism was more common in myopes. 2,21 As in other studies, 2,21 againstthe-rule astigmatism was detected more commonly in mild (moderate) ammetropes.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…As previously reported in other studies, 1,2,21 with-the-rule astigmatism was more common in myopes. 2,21 As in other studies, 2,21 againstthe-rule astigmatism was detected more commonly in mild (moderate) ammetropes.…”
Section: Discussionsupporting
confidence: 72%
“…This higher prevalence of against-the-rule astigmatism decreases with age and with-the-rule astigmatism becomes predominant in preschool and schoolage children. [1][2][3][4]20,32 An increase in the percentage of against-the-rule astigmatism occurs in adulthood and older ages. [5][6][7]17,18,[21][22][23][24][25][26][27][28]33 The same pattern was detected in our population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also few population-based studies of astigmatism in young children [7][8][9], and these have not reported on the components of astigmatism. The relationship between components of astigmatism has also been less well studied.…”
Section: Introductionmentioning
confidence: 99%